Особливості вивчення української мови як іноземної у вищих мистецьких навчальних закладах - Касьяненко, Т.А. (Культура народов Причерноморья, 2013)
У статті розглянуто й визначено особливості вивчення української мови як іноземної у вищих навчальних закладах мистецького профілю, зокрема, реалізацію принципів професійно- орієнтованого підходу до навчання, як домінуючої особливості вивчення української мови як іноземної у мистецьких ВНЗ. Зосереджено увагу на проблемах розробки багатоаспектної моделі підручника для іноземних студентів з української мови для мистецьких ВНЗ. В статье определены особенности обучения иностранных студентов украинскому языку в высших учебных заведениях по направлению «Искусство», в частности, рассмотрена реализация принципов профессионально-ориентированного подхода к обучению украинскому языку в вузах искусств как доминирующей составляющей языкового образования иностранцев, а также сосредоточено внимание на проблемах разработки многоаспектной модели учебника для иностранных студентов по украинскому языку для высших учебных заведений искусств. The article defines the features of teaching Ukrainian language by foreign students in higher education institutions in the direction of "Art”. In particular, itconsideres the implementation of the principles of professional-oriented approach to learning the Ukrainian language in universities of art, as the dominant component of foreign language education. The article also focuses on the development problems of multi- dimensional model of a textbook in Ukrainian language for foreign students in higher education of Arts, which take into account the study specifics, that at this stage are a common problem in the process of studying of Ukrainian language by foreign students regardless of their country of origin. One of the most effective educational tools, which has a multi-faceted capabilities of formation the professionally language competence of foreign students, we assume the creation of a multidimensional model of the electronic textbook.